Pmr (Progressive Muscle Relaxation) terhadap Tingkat Nyeri pada Lansia dengan Rheumatoid Arthritis - Nurfadhila Odja; Nurdiana Djamaluddin; Sri Yulian Hunowu (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to determine the effect of PMR therapy on pain levels in elderly people with RA at the South Kota Community Health Center. The method used was a pre-experimental approach with a one-group pretest-posttest approach. The results showed that before PMR therapy, most respondents experienced moderate pain (24 respondents (77.4%) and severe pain (7 respondents (22.6%). After PMR therapy, pain levels decreased, with most respondents experiencing moderate pain (18 respondents (58.1%) and mild pain (13 respondents (41.9%). The bivariate analysis showed a p-value of 0.000 (<0.05), indicating a significant effect of PMR therapy on pain levels in elderly people with RA. In conclusion, Progressive Muscle Relaxation therapy is effective as a non-pharmacological intervention in reducing pain levels in elderly people with Rheumatoid Arthritis at the South Kota Community Health Center. Keywords: Elderly, Progressive Muscle Relaxation, Rheumatoid Arthritis, Pain Level